2004
DOI: 10.1093/logcom/14.6.801
|View full text |Cite
|
Sign up to set email alerts
|

On Computing Belief Change Operations using Quantified Boolean Formulas

Abstract: In this paper, we show how an approach to belief revision and belief contraction can be axiomatised by means of quantified Boolean formulas. Specifically, we consider the approach of belief change scenarios, a general framework that has been introduced for expressing different forms of belief change. The essential idea is that for a belief change scenario (K, R, C), the set of formulas K, representing the knowledge base, is modified so that the sets of formulas R and C are respectively true in, and consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Our embeddings are somewhat simpler than the embeddings of belief change operations into QBF as done in [4] since DL-PA is a logic of programs. The same argument applies to embeddings of merging problems into MSO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our embeddings are somewhat simpler than the embeddings of belief change operations into QBF as done in [4] since DL-PA is a logic of programs. The same argument applies to embeddings of merging problems into MSO.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 collects some DL-PA expressions that are going to be convenient abbreviations. 4 The program vary(P) nondeterministically changes the truth value of some of the variables in P. Its length is linear in the cardinality of P. So the program vary(P A ); A? accesses all A-valuations that preserve the values of all those variables not occurring in A. Satisfiability of the Boolean formula A can be expressed in DL-PA by the formula vary(P A ); A?…”
Section: Theorem 1 For Every Dl-pa Formula ϕ There Is a Boolean Formmentioning
confidence: 99%
“…It has been shown that this language is useful for expressing a variety of computational paradigms, such as default reasoning [20], circumscribing inconsistent theories [21], paraconsistent preferential reasoning [6], and computations of belief revision operators (see [29], as well as Section 5 below). In this section we show how QBF solvers can be used for computing the ≤ i -preferred repairs of a given database.…”
Section: Computing ≤ I -Preferred Repairs By Qbf Solversmentioning
confidence: 99%
“…QBFs are formulas involving only propositional languages and quantifications over propositional variables. Their application is vast, covering many areas among which are planning [67], verification [12,59], and different computational paradigms for non-monotonic reasoning, such as default reasoning [15], circumscribing inconsistent theories [16] and computations of belief revision operators [36]. In our case, the use of signed theories and QBFs implies that decision problems like skeptical and credulous acceptance of arguments are a matter of logical entailment and satisfiability, which can be verified by existing QBF-solvers.…”
Section: Introductionmentioning
confidence: 99%